Metaphorical nomination in term formation (based on medical terms) - Tleumbetova, D.B.; Ivanova, S.A.; Tugambekova, M.A. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In the article the issue of main peculiarities of metaphorical term functioning is presented. The authors study the principles of nomination of term-metaphors in medical terminology and sources of metaphorisation. Productive metaphorical models based on principles of consistency and anthropocentricity, proving metaphoricity of specialists’ thinking are presented. A particular emphasis is given to mechanisms of metaphorical nomination of medical terms. It is noted that the metaphoric nomination represents a stable mechanism of replenishment of the investigated term system. On the basis of the analysis it is established that anatomical terminology is characterized by the wide use of the whole package of metaphorical models. The most typical models confirm the consistency of this method and the generality nature of the metaphor. It is inferred that the metaphorisation proceeds most actively in those subject groups which are characterized by positive dynamics of emergence and interpretation of new knowledge.
Терминжасаудағы метафоралық номинация (медициналық терминдер материалында)
Метафорическая номинация в терминообразовании (на материале медицинских терминов)
Keywords: metaphor; metaphorisation; metaphorical nomination; medical terminology